Traumatic brain injury and age at onset of cognitive decline in corticobasal degeneration, corticobasal syndrome, and progressive supranuclear palsy. (31st December 2021) - Spiegel, Jonathan; Sone, Je Yeong; Butler, Tracy; Pirraglia, Elizabeth; de Leon, Mony J.
Abstract: Background: Traumatic brain injury (TBI) has been repeatedly shown to be a risk factor for several neurodegenerative diseases. However, no studies have yet examined TBI as a risk factor for corticobasal degeneration (CBD) or corticobasal syndrome (CBS), and few have examined progressive supranuclear palsy (PSP) in relation to TBI. Method: This is a retrospective observational study using the National Alzheimer's Coordinating Centers (NACC) database. TBI status was assessed based on self‐reported history. Clinicians estimate was used for determining age at onset (AAO) of cognitive decline and autopsy examination was used for neuropathological diagnosis of CBD and PSP. The most recent assessment of participants was used as of June 2018, including participant visits which occurred between 2005 and 2018. The NACC dataset includes a total of 38, 249 participants. 101 (14 TBI+) participants were included with clinical (antemortem) diagnoses of PSP and 137 (16 TBI+) with CBS. 2, 743 autopsy samples were also included, including 120 (14 TBI+), 58 (7 TBI+), and 11 (1 TBI+) with neuropathological (autopsy) diagnoses of PSP, CBD, or both, respectively. 181 (21 TBI+) of the participants with autopsy diagnosed PSP or CBD had antemortem cognitive decline. Result: TBI is associated with a significant 4‐year earlier AAO of cognitive decline among participants with an antemortem diagnosis of CBS and a 6‐year earlier AAO in participants with autopsy diagnosed PSP. Additionally, TBI among participants with autopsy diagnosed CBD without concomitant Alzheimer's disease (AD) neuropathology was associated with a 7‐year earlier AAO of cognitive decline (p=.066). History of TBI was not significantly associated with the prevalence of PSP and/or CBD pathology postmortem. Conclusion: This is the first report linking TBI with an earlier onset of cognitive decline in CBS and in neuropathologically defined PSP.